2013
DOI: 10.1039/c2ib20227a
|View full text |Cite
|
Sign up to set email alerts
|

Digital holographic microscopy quantifies the degree of inflammation in experimental colitis

Abstract: Inflammatory bowel diseases including Crohn's disease and ulcerative colitis resemble a large burden for patients due to the chronic course of disease. Therefore, there is an urgent need to explore new potential drugs and to develop new treatment options. Usually, evaluation of therapeutic potential is performed in murine models of colitis with the challenge of a valid assessment of the ongoing inflammation and the therapeutic response. Digital holographic microscopy (DHM) enables stain-free quantitative phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 50 publications
0
44
1
Order By: Relevance
“…For example, 2-D and 3-D RI distributional maps can be utilized in label-free cellular identification (Chalut et al 2012;Jo et al 2015;Jo et al 2014;Jo et al 2017;Yoon et al 2017) and long-term growth monitoring (Bettenworth et al 2014;Chalut et al 2012). In addition, RI itself can be used as a new marker which represents cellular states or abnormalities (Lenz et al 2013;Schürmann et al 2016), and the factors which change the intracellular RI are being actively studied (Ekpenyong et al 2013;Wang et al 2011b).…”
Section: Opportunities and Challenges Of Ri As Imaging Contrastmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 2-D and 3-D RI distributional maps can be utilized in label-free cellular identification (Chalut et al 2012;Jo et al 2015;Jo et al 2014;Jo et al 2017;Yoon et al 2017) and long-term growth monitoring (Bettenworth et al 2014;Chalut et al 2012). In addition, RI itself can be used as a new marker which represents cellular states or abnormalities (Lenz et al 2013;Schürmann et al 2016), and the factors which change the intracellular RI are being actively studied (Ekpenyong et al 2013;Wang et al 2011b).…”
Section: Opportunities and Challenges Of Ri As Imaging Contrastmentioning
confidence: 99%
“…The RI information, for example, was used to quantify the weight loss in the inflammation-induced colitis (Lenz et al 2013). Besides the dry mass information, the measurements of optical phase delay maps of a tissue slice could precisely be utilized to extract the scattering parameters such as scattering coefficients (μs) and anisotropies (g) (Ding et al 2011;Wang et al 2011a;Wang et al 2011b).…”
Section: Hepatologymentioning
confidence: 99%
“…Recently, it has been demonstrated that DHM provides quantitative monitoring of physiological processes through structural analysis and functional imaging which, for example, gives new insight into signaling of cellular water permeability [19], [20], cell morphology changes due to toxins [21][24] and infections [25][27] as well as micro-calcification, cancer and inflammation mediated tissue alterations [12], [28] and bacteria and mammalian single cell growth [29][32].…”
Section: Introductionmentioning
confidence: 99%
“…Because the quantitative optical phase contains quantitative information about morphology and optical properties of the samples, QPI has been widely imported into biological and medical research field in recent years [5]. Its applications of imaging range from small biological cells such as red blood cells [6] and pathological bacteria [7] to large field-of-view samples such as a neuronal network [8] or biological tissues such as a breast tissue, a prostate tissue and colitis-induced murine colon [9,10]. Its application to pathological brain tissue, however, is unprecedented.…”
Section: Introductionmentioning
confidence: 99%